2017
DOI: 10.1002/adma.201605756
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Photovoltaic Devices using Trap‐Controlled Quantum‐Dot Ink prepared via Phase‐Transfer Exchange

Abstract: Colloidal-quantum-dot (CQD) photovoltaic devices are promising candidates for low-cost power sources owing to their low-temperature solution processability and bandgap tunability. A power conversion efficiency (PCE) of >10% is achieved for these devices; however, there are several remaining obstacles to their commercialization, including their high energy loss due to surface trap states and the complexity of the multiple-step CQD-layer-deposition process. Herein, high-efficiency photovoltaic devices prepared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
150
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 58 publications
1
150
0
Order By: Relevance
“…The tunable QD bandgaps, [1][2][3][4][5][6] high film stability in air, [2,3,5,6] and solution processability [2][3][4][5][6] could allow for the fabrication of low-cost, large-area devices. The tunable QD bandgaps, [1][2][3][4][5][6] high film stability in air, [2,3,5,6] and solution processability [2][3][4][5][6] could allow for the fabrication of low-cost, large-area devices.…”
Section: Use Of Lead Sulfide (Pbs) Colloidal Quantum Dot (Qd) Films Amentioning
confidence: 99%
See 4 more Smart Citations
“…The tunable QD bandgaps, [1][2][3][4][5][6] high film stability in air, [2,3,5,6] and solution processability [2][3][4][5][6] could allow for the fabrication of low-cost, large-area devices. The tunable QD bandgaps, [1][2][3][4][5][6] high film stability in air, [2,3,5,6] and solution processability [2][3][4][5][6] could allow for the fabrication of low-cost, large-area devices.…”
Section: Use Of Lead Sulfide (Pbs) Colloidal Quantum Dot (Qd) Films Amentioning
confidence: 99%
“…[5] It has been shown that a significant improvement in QD PV performance can be achieved if the deposited PbS QD films are chemically treated to undergo ligand exchange, replacing OA with shorter ligands, such as halides and short-chain thiols, which leads to high charge conductivities within QD films, boosting the power conversion efficiency of QD PVs. [1][2][3][4] This ink can then be deposited on a substrate to form the QD PV device active layer, [1][2][3][4] with recently reported PbS QD PVs achieving 12% power conversion efficiency (PCE). In a separate synthetic step, OAcapped PbS QDs are exchanged with short ligands in solution and then suspended at a high concentration in a solvent to form an ink.…”
mentioning
confidence: 99%
See 3 more Smart Citations